Trends and Outcomes in Sarcomatoid Renal Cell Carcinoma: Analysis of the National Cancer Data Base - Luke L. Wang; Dhruv Puri; Cesare Saitta; Franklin Liu; Jonathan A. Afari; Margaret F. Meagher; Kevin Hakimi; Mimi V. Nguyen; Aastha Shah; Saeed Ghassemzadeh; James D. Murphy; Juan Javier-Desloges; et al. (European Urology Open Science)
Background and objective: Our aim was to determine the clinical characteristics, temporal trends, and survival outcomes for sarcomatoid-dedifferentiated renal cell carcinoma (sRCC), as sRCC has historically had poor prognosis and a contemporary cohort has not been well characterized in a population-based study. Methods: Data for 302 630 RCC cases from 2010 to 2019 were extracted from the National Cancer Data Base, of which 4.1% (12 329) were sRCC. Trend analyses were conducted using the Cochran-Armitage test. Multivariable analyses were used to assess factors associated with sRCC diagnosis and clinicopathologic characteristics associated with all-cause mortality (ACM). Overall survival (OS) was computed via Kaplan-Meier analysis. Key findings and limitations: sRCC incidence increased from 3.9% in 2010 to 4.1% in 2019 (p = 0.020). The incidence of stage I sRCC increased from 14.5% in 2010 to 19.2% in 2019 (p < 0.001). sRCC diagnosis was associated with male sex, tumor size, cN1 status, and collecting duct histology. Worse ACM in localized sRCC was associated with age, tumor size, cN1 stage, collecting duct histology, and positive surgical margins; and was inversely associated with partial nephrectomy (hazard ratio [HR] 0.61, 95% confidence interval [CI] 0.49–0.76; p < 0.001). Worse ACM in metastatic sRCC was associated with age, tumor size, cN1, collecting duct histology, positive surgical margins, and no surgery at the primary site (HR 1.66, 95% CI 1.20–2.30; p = 0.006). The 5-yr OS rates for stage I, stage II, stage III, and stage IV sRCC were 74%, 63%, 42%, and 16%, respectively (p < 0.001). Conclusions and clinical implications: The proportion of sRCC cases overall and of stage I sRCC cases increased from 2010 to 2019, supporting the hypothesis of stage migration and the potential for early sarcomatoid dedifferentiation. Further studies on the causal mechanisms underpinning better survival after partial nephrectomy in localized disease and after cytoreductive surgery in metastatic disease are warranted. Patient summary: We analyzed trends and outcomes for a type of aggressive kidney cancer (sarcomatoid renal cell carcinoma, sRCC) using records from the National Cancer Data Base. We found that the percentage of sRCC cases among all kidney cancers increased from 2010 to 2019. Factors such as tumor size and patient age were linked to worse survival. Surgery to remove the cancer was linked to better survival.